The effect of thyroid hormone therapy on muscle function, strength and mass in older adults with subclinical hypothyroidism—an ancillary study within two randomized placebo controlled trials. (27th January 2023) - Netzer, Seraina; Chocano-Bedoya, Patricia; Feller, Martin; Janett-Pellegri, Camilla; Wildisen, Lea; Büchi, Annina E; Moutzouri, Elisavet; Rodriguez, Elena Gonzalez; Collet, Tinh-Hai; Poortvliet, Rosalinde K E; Mc Carthy, Vera J C; Aeberli, Daniel; et al.
Abstract: Background: loss of skeletal muscle function, strength and mass is common in older adults, with important socioeconomic impacts. Subclinical hypothyroidism is common with increasing age and has been associated with reduced muscle strength. Yet, no randomized placebo-controlled trial (RCT) has investigated whether treatment of subclinical hypothyroidism affects muscle function and mass. Methods: this is an ancillary study within two RCTs conducted among adults aged ≥65 years with persistent subclinical hypothyroidism (thyrotropin (TSH) 4.60–19.99 mIU/l, normal free thyroxine). Participants received daily levothyroxine with TSH-guided dose adjustment or placebo and mock titration. Primary outcome was gait speed at final visit (median 18 months). Secondary outcomes were handgrip strength at 1-year follow-up and yearly change in muscle mass. Results: we included 267 participants from Switzerland and the Netherlands. Mean age was 77.5 years (range 65.1–97.1), 129 (48.3%) were women, and their mean baseline TSH was 6.36 mIU/l (standard deviation [SD] 1.9). At final visit, mean TSH was 3.8 mIU/l (SD 2.3) in the levothyroxine group and 5.1 mIU/l (SD 1.8, P < 0.05) in the placebo group. Compared to placebo, participants in the levothyroxine group had similar gait speed at final visit (adjusted between-group mean difference [MD] 0.01 m/s, 95% confidence interval [CI] −0.06 to 0.09), similar handgrip strength at one year (MD −1.22 kg, 95% CI −2.60 to 0.15) and similar yearly change in muscle mass (MD −0.15 m 2, 95% CI −0.49 to 0.18). Conclusions: in this ancillary analysis of two RCTs, treatment of subclinical hypothyroidism did not affect muscle function, strength and mass in individuals 65 years and older.